Intelligent AGV with navigation, object detection and avoidance in an unknown environment - Boje, Ellenor Petronella (Bloemfontein : Central University of Technology, Free State, 2007)
The latest technological trend worldwide, is automation. Reducing human labour and introducing robots to do the work is a pure business decision. The reason for automating a plant can be some, or all, of the following: Improve productivity Reduce labour and equipment costs Reduce product damage System reliability can be monitored Improves plant safety When the automation process is started, Automatic Guided Vehicles (AGVs) will be one of the first commodities that can be used. The reason for this is that they are so versatile. They can be programmed to follow specific paths when moving material from one point to another and the biggest advantage of all is that they can operate for twenty four hours a day. Automatic Guided Vehicles are developed for many different applications and therefore many different types of AGVs are available. All AGVs are equipped with sensors so that they are able to “see” what is happening around them. Since the AGV must be able to function without any human help or control, it must be able to navigate through the work environment. In this study a remote control car was converted to an AGV and thorough research was done on the different types of sensors that can be used to make the AGV more intelligent when it comes to navigating in an unknown environment.
Thesis (M.Tech.) - Central University of Technology, Free State, 2007
Keywords: Central University of Technology, Free State - Dissertations; Robots - Control systems; Robots - Motion; Robots - Programming; Automation; Navigation computer (Aeronautical instrument); Object-oriented methods (Computer science); Dissertations, academic - South Africa - Bloemfontein